Why so negative? Negative party positioning in spatial models of voting - Felix Hoch; Kim Leonie Kellermann (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2020)
Why should political parties say what they do not want instead of saying what they want? In this paper, we introduce the concept of negative positioning into spatial models of voting and discuss its relevance as a campaigning tool in European multiparty systems. By negative positioning, we refer to the rejection, denial or criticism of opposing positions on a political issue scale without providing information on what a party's own position is instead. We argue that negative positioning is an attractive tool in reaction to high issue salience among voters as it allows to acknowledge the respective issue without costly commitment to or design of own policy proposals. We provide a first empirical test of our concept for elections held in 26 European countries between 2002 and 2018, examining immigration as an issue with a highly volatile salience. We use data on voter issue salience from the Eurobarometer and on party positions from the Manifesto Project Database. Indeed we find that if an issue is highly salient among voters, parties increase the share of negative positioning on that issue in their manifestos. Interestingly, negative positioning is more prevalent among smaller, opposition and extreme parties.
Keywords: C33; D71; D72; D78; 330; issue salience; party positioning; negative positioning; negative campaigning